Chanter la Saint-Barthélemy. Les voix catholiques radicales et la mémoire urbaine du massacre - Tatiana Debbagi Baranova (Etudes Epistémè)
This article examines the songs composed and sung by Catholics after the St Bartholomew's Day massacre. It was a favoured mode of expression for radical urban circles, which allowed a specific discourse on the massacre, quite distinct from the royal interpretation. These songs mobilised the radical imagination by glorifying the urban communities that had wiped out heresy at the behest of the king and in accordance with divine will. The article shows how this discourse, sung in the streets of Paris and Lyon in the days following the massacre, resurfaced in new, specific circumstances to make the radicals' opinion heard, for example, on the arrival of Henri III in the city of Paris in 1575. It also seeks to measure their longevity. Il establishes that the most radical songs, referring to the massacring urban community, were no longer published after the Peace of Beaulieu (1576), but survived in zealous circles at least until the League. Other, more consensual songs, such as Les Traistres de La Rochelle, were printed in collections of chansons d'amour and chansons de guerre (songs of love and war), marking the passage of catholic discourse on the massacre into the sphere of entertainment and testifying to the habituation of urban Catholic society to the idea of the legitimacy of violence against the "enemies" of God and the king.